2010
DOI: 10.1098/rspb.2010.1399
|View full text |Cite
|
Sign up to set email alerts
|

Over-imitation is better explained by norm learning than by distorted causal learning

Abstract: In over-imitation, children copy even elements of a goal-directed action sequence that appear unnecessary for achieving the goal. We demonstrate in 4-year olds that the unnecessary action is specifically associated with the goal, not generally associated with the apparatus. The unnecessary action is performed flexibly: 4-year olds usually omit it if it has already been performed by an adult. Most 5-year olds do not verbally report the unnecessary action as necessary when achieving the goal, although most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 53 publications
7
164
1
2
Order By: Relevance
“…Consequently, it is necessary to be interpret these findings in a context of the goaldirected imitation literature with some caution. In detecting a contraction bias, we find that children are imitating conservatively, which appears at some odds with literature suggesting that children are more likely to over-imitate (Horner & Whiten, 2005;McGuigan et al, 2010) and that they may do so to comply with prescriptive norms or cultural expectations (Kenward, Karlsson, & Persson, 2011;Nielsen & Blank, 2011). In our study however, the degree of error was not the result of intentional action selection but rather a mismatch between magnitudes of perceived and executed actions, presumably as a result of the functioning of the visuomotor system.…”
Section: Discussioncontrasting
confidence: 56%
“…Consequently, it is necessary to be interpret these findings in a context of the goaldirected imitation literature with some caution. In detecting a contraction bias, we find that children are imitating conservatively, which appears at some odds with literature suggesting that children are more likely to over-imitate (Horner & Whiten, 2005;McGuigan et al, 2010) and that they may do so to comply with prescriptive norms or cultural expectations (Kenward, Karlsson, & Persson, 2011;Nielsen & Blank, 2011). In our study however, the degree of error was not the result of intentional action selection but rather a mismatch between magnitudes of perceived and executed actions, presumably as a result of the functioning of the visuomotor system.…”
Section: Discussioncontrasting
confidence: 56%
“…A subsequent study showed that children enforce norms learned in this way on ingroup members but not on outgroup members (Schmidt, Rakoczy, & Tomasello, submitted). Taken together, these studies show that in these kinds of situations, children not only learn the actions involved in the demonstration, they learn how members of their particular culture ought to perform the specified behavior (see also Kenward et al, 2011, for further evidence of the role of norms in imitation).…”
Section: Learning Goals and Social Goals Are Both Importantmentioning
confidence: 99%
“…Lyons (2009) attempts to explain the existence of selective copying by arguing that actions not directed toward objects (e.g., those used in the Bekkering et al, 2000 study) may be copied selectively. However, this theory, along with the somewhat related theory of Kenward, Karlsson, and Persson (2011) that children learn a generalized norm that unnecessary actions ought to be performed, are brought into question by data demonstrating that some intentionally produced, objectdirected actions are imitated selectively. For example, in one demonstration of this, DiYanni and Kelemen (2008) presented 2-to 4-year-old children with a demonstration in which a model intentionally rejected a functionally affordant tool in favor of a nonaffordant tool.…”
Section: Theoretical Explanations For Selective and Exact Copying Behmentioning
confidence: 99%
“…Recent explanations of overimitation have focused on the social nature of this behavior, as a sign of social affiliation or conformity to a social norm (Kenward, Karlsson, & Persson, 2010;Marsh, Pearson, Ropar, & Hamilton, 2013). Social cues, such as demonstrator status, have been shown to modulate overimitation.…”
Section: Overimitation Behaviormentioning
confidence: 99%